A case report of skeletal fluorosis leading to cervical compressive myelopathy and a review of literature - Abhishek Singhai; Vishnu N Mishra; Vaibhav Ingle (MGM Journal of Medical Sciences, 2022)
Fluorosis is a public health problem that is caused by excess intake of fluoride through ground/deep bore water. It gets deposited in the bones, teeth, and soft tissues. Fluoride in the human body acts as a “double-edged sword.” Fluoride is beneficial in small amounts but toxic in large amounts. People who have consumed 10–20 mg of fluoride per day for more than 10–20 years may develop crippling skeletal fluorosis. Stiffness and pain in the major joints, including the neck, back, hips, and knees, reduce mobility. The bone structure may change and ligaments may calcify in extreme cases, resulting in muscular weakness and pain. Here, we have reported a case of chronic quadriparesis due to compressive cervical myelopathy. After extensive workup, diagnosis of skeletal fluorosis was made.